Improving Learning objects reusability through automatic generation web services - Kanagwa, Benjamin; Agaba, Joab; Tuheirwe, Doreen; Lunkuse, Susan (My University, 2011)
To support current needs of fl exible e-learning environments, there is need for improved techniques to create, mix and fi nd and compose user e-learning resources. These techniques need to take advantage of the existing web infrastructure and tools to further provide seamless integration with the Internet where most learning objects live. The main enabler has been standardization efforts built around the notion of metadata. However, this standardization effort is not naturally supported by the web infrastructure where e-learning operates. In this paper, we take advantage of the widespread adaptability of web services to provide fl exible and composable learning objects as services. We automatically transform learning objects and expose them as services, thereby allowing Learning Management Systems (LMS) to take advantage of the inherent flexibility, agility and mature tools within the domain of web services.
Keywords: web services; learning objects; re-use; e-learning